Characteristics of pediatric patients with multiple sclerosis and related disorders infected with SARS-CoV-2. (April 2023) - Schreiner, Teri; Wilson-Murphy, Molly; Mendelt-Tillema, Jan; Waltz, Michael; Codden, Rachel; Benson, Leslie; Gorman, Mark; Goyal, Manu; Krupp, Lauren; Lotze, Tim; Mar, Soe; Ness, Jayne; et al.
Background: Pediatric patients with multiple sclerosis (POMS) and related disorders, clinically isolated syndrome (CIS), myelin oligodendrocyte glycoprotein antibody disorder (MOGAD), and neuromyelitis optica spectrum disorder (NMOSD), are commonly treated with immunosuppressants. Understanding the impact of SARS-CoV-2 infection in patients may inform treatment decisions. Objective: Characterize SARS-CoV-2 infection prevalence and severity among a cohort of patients with POMS and related disorders, as well as the impact of disease-modifying therapies (DMTs). Methods: POMS and related disorders patients enrolled in a large, prospective registry were screened for COVID-19 during standard-of-care neurology visits. If confirmed positive of having infection, further analysis was undertaken. Results: Six hundred and sixty-nine patients were surveyed between March 2020 and August 2021. There were 73 confirmed COVID-19 infections. Eight of nine hospitalized patients (89%), and all patients admitted to the ICU were treated with B cell depleting therapy. The unadjusted odds ratio of hospitalization among those who tested positive of having had COVID-19 was 15.27 among those on B-cell-depleting therapy ( p = 0.016). Conclusions: B-cell-depleting treatment was associated with a higher risk of COVID-19, higher rates of hospitalization, and ICU admission, suggesting this therapy carries a higher risk of severe infection in POMS and related disorders.